A Spatial Decision Support Tool to Study Risks and Opportunities of Complex Environmental Systems - Ferretti, Valentina; Bottero, Marta; Mondini, Giulio (Journal of Environmental Accounting and Management, 2026)
An important problem arising when assessing territorial systems is linked to their complexity. This requires multidimensional approaches for the evaluation in order to obtain concise final judgments. Moreover, when dealing with territorial systems, the analysis of the geographical patterns of the elements under investigation plays a fundamental role. This paper proposes an integrated approach for the analysis of a complex environmental system based on the use of Multicriteria-Spatial Decision Support Systems (MC-SDSS). MC-SDSS consist in the integration of Geographic Information Systems (GIS) and Multicriteria Decision Aiding (MCDA) techniques. In particular, starting from a real case related to a mountain area in Northern Italy, the present paper explores the potentialities of the MC-SDSS methodology for supporting the definition of future transformation scenarios.